“Radiation Recall Phenomenon” with Novel Cytotoxic Agents: An Emerging Trend in the Last Decade - Mandal, Avik; Singh, Pritanjali; Tandon, Sarthak; Singh, Dharmendra (Indian Journal of Medical and Paediatric Oncology, 2021)
Radiation recall phenomenon (RRP) is an acute inflammatory reaction manifested in the previously irradiated tissues after the administration of various pharmacologic compounds. While skin manifestations are the most common clinical features, patients may also present with visceral recall events including pneumonitis, hematuria, myopathy, and mucositis if any particular organ was exposed to the prior radiation portals. This article has reviewed the published case reports, case series, abstracts, and poster presentations in the past 10 years in any language on RRP caused by various novel cytotoxic drugs including immunotherapies, molecularly targeted agents, and unconventional chemotherapies. We retrieved the data through the literature search of MEDLINE and PubMed using the keywords “radiation,” “recall,” “targeted therapy,” and “immunotherapy,” and references identified in retrieved articles were also used for further search of the literature. With the increasing use of unconventional, novel cytotoxic agents and targeted molecules, concurrent or sequentially with radiation, we expect more incidences of RRP in future that may present with either dermatological or visceral recall reactions.
Keywords: immunotherapy; radiation; recall; targeted therapy